Milk Fat Globule‐Epidermal Growth Factor 8 (MFG‐E8) Is a Novel Anti‐inflammatory Factor in Rheumatoid Arthritis in Mice and Humans. (9th November 2015) - Albus, Elise; Sinningen, Kathrin; Winzer, Maria; Thiele, Sylvia; Baschant, Ulrike; Hannemann, Anke; Fantana, Julia; Tausche, Anne‐Kathrin; Wallaschofski, Henri; Nauck, Matthias; Völzke, Henry; Grossklaus, Sylvia; et al.
ABSTRACT: Milk fat globule‐epidermal growth factor 8 (MFG‐E8) is an anti‐inflammatory glycoprotein that mediates the clearance of apoptotic cells and is implicated in the pathogenesis of autoimmune and inflammatory diseases. Because MFG‐E8 also controls bone metabolism, we investigated its role in rheumatoid arthritis (RA), focusing on inflammation and joint destruction. The regulation of MFG‐E8 by inflammation was assessed in vitro using osteoblasts, in arthritic mice and in patients with RA. K/BxN serum transfer arthritis (STA) was applied to MFG‐E8 knock‐out mice to assess its role in the pathogenesis of arthritis. Stimulation of osteoblasts with lipopolysaccharide (LPS) and tumor necrosis factor (TNF)‐α downregulated the expression of MFG‐E8 by 30% to 35%. MFG‐E8‐deficient osteoblasts responded to LPS with a stronger production of pro‐inflammatory cytokines. In vivo, MFG‐E8 mRNA levels were 52% lower in the paws of collagen‐induced arthritic (CIA) mice and 24% to 42% lower in the serum of arthritic mice using two different arthritis models (CIA and STA). Similarly, patients with RA ( n  = 93) had lower serum concentrations of MFG‐E8 (–17%) compared with healthy controls ( n  = 140). In a subgroup of patients who had a moderate to high disease activity ( n  = 21), serum concentrations of MFG‐E8 rose after complete or partial remission had been achieved (+67%). Finally, MFG‐E8‐deficient mice subjected to STA exhibited a stronger disease burden, an increased number of neutrophils in the joints, and a more extensive local and systemic bone loss. This was accompanied by an increased activation of osteoclasts and a suppression of osteoblast function in MFG‐E8‐deficient mice. Thus, MFG‐E8 is a protective factor in the pathogenesis of RA and subsequent bone loss. Whether MFG‐E8 qualifies as a novel biomarker or therapeutic target for the treatment of RA is worth addressing in further studies. © 2015 American Society for Bone and Mineral Research.